OVERVIEW OF CARIES STATUS IN STUNTED TODDLERS AGED 6-23 MONTHS - Hani Adriani, Retno; Nurrachmawati, Annisa; Anggraeni Gunawan, Ike (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : : Stunting in Indonesia is a major public health problem caused by several factors, one of the most common factors is malnutrition conditions. Recent studies have stated that poor and unbalanced nutrition has a positive relationship with the severity of dental caries, Apart from that, there is a reciprocal relationship between caries and stunting Objective : This study aims to describe caries status in stunted toddlers Research Methods/ Implementation Methods : Observational study with a case control approach. The population includes 3 sub-districts in Palaran District. The number of samples in this study was 90 cases: 180 controls with a total of 270 respondents, mothers of toddlers. Variables are caries index of toddlers. The instrument used was examined using def-t indexs to measure the dental caries by toddlers patient direct inspection. Data analyze in univariat. Results : The results showed that the caries index of toddlers was found to be predominantly low, with a higher prevalence (20%) observed in stunted toddlers compared to non-stunted toddlers (14.4%) Conclusion/Lesson Learned : The difference found in stunted toddlers and non-stunted toddlers was the difference in Caries indexs. For this reason, interventions that integrate oral health with improved nutritional intake are needed, especially for stunted toddlers.